EFL teachers’ Perceptions about Intercultural communicative competences and their practices in English classes on the context of current migration waves in Bogotá. (2020)
To explore, How EFL teachers promote the Intercultural Communicative Competence to develop awareness, acceptance and respect among members from other cultures and backgrounds in the context of current migration waves in Bogotá.